Experimental investigation on the bearing behaviour of aluminium sub-heads in façade systems. (November 2020) - Akbari, Masoumeh; Gunalan, Shanmuganathan; Gilbert, Benoit P.; Guan, Hong; Baleshan, Balachandren
Abstract: In the building sector, the application of aluminium alloys in load carrying structures as well as building envelopes has received attention over the past decades. Under wind loading, the vertical members of window walls known as mullions, carry the horizontal load transferred from the glass panels. This load is then transferred to the sub-heads at the top and the sub-sills at the bottom which are connected to the structure. The aluminium sub-head flange due to its long length is susceptible to bending (bearing failure) under this loading condition, a phenomenon that has hitherto not been adequately researched. Hence the performance of aluminium sub-head sections subjected to bearing failure was investigated through a series of 42 tests. This study mainly explores the impacts of parameters such as the bearing width, the loading and boundary conditions, as well as various geometric sections, on the bearing failure of aluminium sub-heads. The significant failure modes observed in the tests were yielding at web-flange junction and slipping of the bearing plate. Currently, no design rules are available to predict the bearing capacity of aluminium sub-heads. Hence a comparison of the ultimate bearing capacities of the test results and the design capacities obtained using the available cold-formed steel design specifications was performed. The code-predicted design strengths were found to be overly conservative for aluminium sub-head sections in window walls. Therefore, new design equations were developed to ensure safe, economic and reliable design of aluminium sub-heads using a wide range of bearing capacity data obtained from the experimental studies. The proposed design rules were found to be in precise agreement with the experimental values. Highlights: Experimentally investigated the bearing behaviour of aluminium sub-heads in façade systems. Considered various section geometries, bearing widths, bolt connections, loading and boundary conditions. Sub-head sections failures were due to yielding of the web-flange junction and slipping of bearing plate. Current cold-formed steel design equations are overly conservative for aluminium sub-heads. New design rules were proposed for aluminum sub-heads and calibrated using test results.